Mitochondria-associated regulation in adipose tissues and potential reagents for obesity intervention - Zheng, Yali; Yang, Ni; Pang, Yueshan; Gong, Yanju; Yang, Hong; Ding, Weijun; Yang, Hongya (Frontiers in Endocrinology, 2023)
Obesity has become a major health problem worldwide. Adipose tissues, which function in energy metabolism and endocrine organs, are closely linked to metabolic syndromes including obesity, insulin resistance and type 2 diabetes. Studies have shown that mitochondrial dysfunction is associated with the white adipose tissue (WAT) phenotype and differentiation in obesity. Brown adipose tissue (BAT) and BAT-like adipose tissue, commonly known as ‘beige’ adipose tissue, dissipate nutritional energy as heat by uncoupling protein 1 (UCP1). To obtain an overview of mitochondrial regulation in adipose tissues, a comprehensive review was conducted. We searched three databases using terms including obesity, mitochondria, WAT and BAT and identified 568 publications. Of these, 134 papers met the preliminary selection criteria, 97 were selected after a full-text review, and 6 were identified after additional searches. Further analysis revealed that mitochondria played a key role in adipose tissue metabolism and energy homeostasis, including potential therapeutic agents for obesity. This review focused on the mitochondria-related regulation of adipose tissues, which facilitates the treatment of metabolic diseases, including obesity.